2018
DOI: 10.1016/j.jor.2018.05.042
|View full text |Cite
|
Sign up to set email alerts
|

Long-term outcome after all inside meniscal repair using the FasT-Fix system

Abstract: At 12 years' follow-up 73% had a successful surgery. KOOS was significantly better within isolated meniscus tears. Both groups showed no difference in the TAS. There were no differences regarding failure rate in the comparison of simultaneous or delayed ACL-reconstruction.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
39
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 28 publications
(41 citation statements)
references
References 28 publications
0
39
0
2
Order By: Relevance
“…The overall failure rate of 22.5% is consistent with previous reports. 3,14,16,17,19,26,38 Lateral Repair Lateral repairs resulted in less failure than medial repairs that have nearly a 4 times higher risk of failure. This is supported by data from a recent systematic review, 27 which concluded that lateral repairs result in fewer reoperations than medial repairs.…”
Section: Meniscal Suturesmentioning
confidence: 99%
“…The overall failure rate of 22.5% is consistent with previous reports. 3,14,16,17,19,26,38 Lateral Repair Lateral repairs resulted in less failure than medial repairs that have nearly a 4 times higher risk of failure. This is supported by data from a recent systematic review, 27 which concluded that lateral repairs result in fewer reoperations than medial repairs.…”
Section: Meniscal Suturesmentioning
confidence: 99%
“…In this study there was a gender difference in failure rate with a higher failure rate in males, however the cause of this is unclear. This differs to the results of Zimmerer [12]. In their long term outcome study using the Fast-Fix ™ system they noted a statistically higher failure rate for women than men (40 failures in women 23 failures in men) where failure was de ned as a new operation on the same meniscus.…”
Section: Discussionmentioning
confidence: 67%
“…The mechanism of injury may re ect the quality of the meniscus and its ability to hold the meniscal suture device. Zimmerer [12] found a correlation between soccer and indoor sports as a mechanism of injury and subsequent long term failure of meniscal repair with the Fast-x system.…”
Section: Discussionmentioning
confidence: 99%
“…Of the 11 studies, only one demonstrated a significant difference in meniscus repair failure risk by sex. Zimmerer et al found a higher failure risk in females, with 11 of 23 (48%) females noted to have failed meniscus repairs versus 6 out of 40 (15%) males with failed repairs (p=0.0076) 24. Given the different findings and relatively low follow-up (less than 20%) in this study, the meta-analysis of clinical signs of repair failure was repeated with this study excluded and again no difference in failure risk was noted between male and females (OR 1.20, 95% CI 0.76 to 1.89, p=0.43).…”
Section: Resultsmentioning
confidence: 98%